2016
DOI: 10.1002/adv.21703
|View full text |Cite
|
Sign up to set email alerts
|

Influence of NiFe Alloy Nanopowder on Electromagnetic and Microwave Absorption Properties of MWCNT/Epoxy Composite

Abstract: Nanocomposite absorbers based on dielectric/magnetic materials are prepared by in situ incorporation of MWCNTs and NiFe alloy nanopowder into epoxy matrix. SEM micrographs and EDAX studies of these nanocomposites clearly revealed the incorporation of MWCNTs/NiFe nanoparticles in the epoxy matrix. Dielectric measurement revealed that the real part of permittivity and permeability of NiFe-filled MWCNT composites increased with an increase in NiFe concentration. The consolidated loss tangent values revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…3,10,12 The solution is then brought to a probe sonicator and sonication is done at 50 MHz for a 90-min time period. The sonication time is chosen based on previous research studies 3,10,12,15,22 which showed maximum graphene dispersion in the base fluid. The sonicated graphene/epoxy solution thus obtained is added to hardener.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…3,10,12 The solution is then brought to a probe sonicator and sonication is done at 50 MHz for a 90-min time period. The sonication time is chosen based on previous research studies 3,10,12,15,22 which showed maximum graphene dispersion in the base fluid. The sonicated graphene/epoxy solution thus obtained is added to hardener.…”
Section: Methodsmentioning
confidence: 99%
“…The EM properties of single-layered composites filled with 0-2.5 wt% MWCNT have been measured experimentally in the previous studies. 22 Also, the fabricated graphene/epoxy single-layered structures were brought to measure EM properties using the waveguide measurement technique. Here, X-band waveguides were used to measure EM properties and the network analyzer was calibrated using the TRL technique.…”
Section: Em Properties Of Single-layered Compositementioning
confidence: 99%
See 1 more Smart Citation
“…According to the transmission line theory, microwave absorption characteristics are highly dependent on the complex permittivity and complex permeability of materials. The electromagnetic parameters of functional particle Fe 3 O 4 -rGO are quite different from those of resin and fiber, while the electromagnetic parameters of resin/fiber composites can be improved to a certain extent by increasing its filling amounts [35,36], thereby obtaining better EMW absorbing abilities. The dielectric properties of GF/EP composites filled with different functional particle As is known to all, the real parts (ε′ and μ′) of electromagnetic parameters represent their storage capacities to electromagnetic energy, while the imaginary parts (ε″ and μ″) show their loss capacities to electromagnetic energy [37].…”
Section: Absorbing Property and Mechanism Of Single Layer Fe 3 O 4 -Rmentioning
confidence: 99%
“…Iron based intermetallic alloy such as FeNi [1], FeCo [2,3], FeCr [4] and Fe-Si-Al [5][6][7] etc. have received extensive attention as EM absorbing functional filler materials due to their advantage of high permeability in GHz region and good thermal stability at higher temperature.…”
Section: Introductionmentioning
confidence: 99%